Balto II Wolf quest (Willowdale, Ontario: Universal Studios Canada, 2000)
Part husky/part wolf, Balto knows what it means to hear "the call of the wild." So when his headstrong young daughter, Aleu, discovers her own wolf heritage, Balto understands she must follow her heart. Now, deep in the Alaskan wilderness, Aleu will seek her own path, tangle with a renegade wolf pack leader and--with a little help from Dad--fulfill her own heroic destiny!
Sequel to: Balto.
Voices: David Carradine, Lacey Chabert, Mark Hamill, and Peter MacNicol.
Rated G.
VHS.
Closed-captioned.
Keywords: Feature films; Children's films; Animated films; Video recordings for the hearing impaired